Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the drivers of firm productivity growth in Spain. Spain's weak productivity performance has been linked to the dominance of many low-productivity small firms and inefficient allocation of resources. The biggest gain can be expected from lowering regulatory barriers to competition and the cost of doing business, including at the regional level. Further improving the access to equity and credit financing, in particular for innovative start-up companies, and addressing potential disincentive effects of size-contingent rules, can also make important contributions to raising productivity growth. Supporting innovation through increasing the efficiency of Research and Development (R and D) incentives and enhancing the private R and D investment should generate positive spillovers, which are difficult to capture empirically.